SISTEM PRODUKSI AGROINDUSTRI KOPI ARABIKA (STUDI KASUS PT SINAR MAYANG LESTARI, KECAMATAN PANGALENGAN, KABUPATEN BANDUNG - Lia, Fransisca; Perdana, Tomy (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2017)
The production system is a system found in the company to change a physical product from the input to the output. PT. Sinar Mayang Lestari is an arabica coffee producer which is experiencing an increase in demand every year. Increasing demand on green bean arabica in 2017, will affect the production system undertaken by PT Sinar Mayang Lestari. This research aims to find out the production system in PT. Sinar Mayang Lestari for coffee processing. This research used qualitative research and descriptive analysis. The results of the study showed that production system in PT Sinar Mayang Lestari consists of input, process, output, and feed back for the company. However, the production system is not optimal yet because the utilization of processing machines does not match the installed capacity. The company needs to set aproduction planning to overcome the increased demand, so that the production system can be done optimally.